Experimental validation of a shape-memory alloy slat-cove filler: Structural response and computational model development. (October 2020) - Patterson, Ryan; Scholten, William; Strganac, Thomas; Turner, Travis; Hartl, Darren
Current and expected Federal Aviation Administration regulations are pressuring the aerospace industry to develop new technologies that reduce aeroacoustic emissions, which may affect the health and well-being of community members. With recent technological advancements reducing noise emissions from aircraft engines, airframe noise sources now represent a large component of the total emitted noise during approach and landing. This research investigates a shape-memory alloy slat-cove filler concept, which is a promising noise reduction technology for the leading-edge-slat high-lift system. Aerodynamic and structural experiments are conducted with the purpose of characterizing response under relevant flow conditions. A model-scale wing section prototype was treated with a slat-cove filler and used to compare aerodynamic effects of the shape-memory alloy treatment at multiple settings. It is shown that the addition of the slat-cove filler does not detrimentally impact the aerodynamic response of the wing prototype and actually resulted in a higher lift-to-drag ratio. Aerostructural experiments were conducted incorporating Digital Image Correlation measurements and displacement measurements from a custom-designed system based on a laser displacement sensor. These experiments determined the structural response of the shape-memory alloy slat-cove filler during a typical retraction/deployment cycle under relevant wind tunnel test conditions and compared to results from a finite element analysis model.